Analisis Efisiensi Anggaran Tuberkulosis dari Negara Berbeban Tinggi Penyakit Tuberkulosis - Estro Dariatno Sihaloho; Adiatma Y. M. Siregar (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2019)
Tuberculosis remains a major global health problem and ranks as the second leading cause of death from infectious disease worldwide. Countries devote their budgets to overcome the tuberculosis problem. An efficient use of these budgets will arguably reduce the number of tuberculosis cases and eventually give a positive impact to the economy. This paper aims it aims to estimate the technical efficiency scores of tuberculosis funds on high-burden countries by using Data Envelopment Analysis (DEA) method. Further, this study analyzes other environmental factors that are crucial to increase the efficiency scores by using Tobit method. DEA shows that some countries exhibit high efficiency scores while others exhibit low efficiency scores. It also informs how countries use funds to maximize their results. Meanwhile, the Tobit estimation shows that taxing cigarettes and committing budgets to control tobaccos have positive marginal effects on technical efficiency scores.